ANALISA KESALAHAN SCANNING ARAH ROLLING PLATE PADA MATERIAL TMCP ( THERMO MECHANICAL CONTROL PROCESS ) TERHADAP INTERPRETASI LOKASI CACAT DENGAN METODE ULTRASONIC TESTING - Indrianto, Totok Tjatoer; Susilo, Trisno; Hilmy , Zakwan (UNIMAR AMNI Semarang, 2025)
TMCP (Thermo-Mechanical Control Process) material, also called anisotropic steel, has recently been used frequently for industrial needs in ship construction, onshore and offshore fabrication. Where TMCP material has different characteristics in its wave propagation speed (velocity) in the material between the direction of plate rolling (rolling direction) which is parallel or longitudinal direction and the transverse direction. This causes the refraction angle of wave propagation to change, thus making the appearance of an indication different on the monitor screen when Ultrasonic Testing (UT) is carried out. The methodology used for this study is to use the literature study method and verification of test results. Where in verifying using the manual ultrasonic testing (MUT) procedure in accordance with DNVGL-CG-0051 revision 2015. The expected results in this study are to provide knowledge about the characteristics of TMCP material and its effects on ultrasonic testing. As well as calibration techniques, how to name saved files and ultrasonic testing on TMCP materials, so that there are no errors in interpreting an indication.